A Study Into the Acceptance Level of Corporate Governance Code 2008 by Dutch Listed Companies - Gupta, Ambrish (Indian Journal of Finance, 2019)
This paper was written with the twin objectives of providing insights into the Dutch Corporate Governance Code 2008 and analyzing the acceptance and compliance level of the Code by the listed Dutch companies. The Code was first formulated in the year 2003. It contains principles, best practice provisions pursuant to principles, and explanatory notes. It was amended in 2008 and recently again in 2016. The 2016 changes are effective beginning financial year 2017, the compliance outcome of which will be known only in 2019. The frequent reviews and modifications of the Code reflect, among other things, the willingness and the ability of various stakeholders in The Netherlands to keep their corporate governance principles and practices in line with the latest thinking and developments on the subject. Furthermore, the almost 100% compliance of the Code by the listed companies is really heartening and reflects its widest possible acceptance and ,therefore, the highest success rate of its key principles and provisions of best practices. The transitional preview of the amended 2016 Code re-enforces its widest acceptance and compliance in the coming years too. SEBI will also do well to prepare such annual compliance performance studies.